2018
DOI: 10.1039/c7tx00305f
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the toxic potential of arecoline toward the third instar larvae of transgenicDrosophila melanogaster (hsp70-lacZ) Bg9

Abstract: Arecoline is the key component of areca nut and has been suggested as a carcinogenic agent. In the present study, the third instar larvae of transgenic were allowed to feed on a diet having 5, 10, 20, 40 and 80 μM arecoline for 24 h. After the completion of 24 h, the larvae were subjected to ONPG assay, X-gal staining, trypan blue exclusion test, oxidative stress markers, and apoptotic and comet assays. A dose-dependent increase in the β-galactosidase activity, tissue damage, glutathione-S-transferase (GST) ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 59 publications
1
5
0
Order By: Relevance
“…But still its toxic effects on the central nervous system are warranted. In our study, it showed the toxic effects in the third instar larvae of transgenic Drosophila melanogaster (hsp70-lacZ) Bg 9 (Shakya & Siddique, 2018). The study performed by Shih et al (2010) on the cultured rat primary cortical neurons showed that it is potent in inducing apoptotic death by attenuating an antioxidant defence system and enhancing the oxidative stress.…”
Section: Introductionsupporting
confidence: 49%
“…But still its toxic effects on the central nervous system are warranted. In our study, it showed the toxic effects in the third instar larvae of transgenic Drosophila melanogaster (hsp70-lacZ) Bg 9 (Shakya & Siddique, 2018). The study performed by Shih et al (2010) on the cultured rat primary cortical neurons showed that it is potent in inducing apoptotic death by attenuating an antioxidant defence system and enhancing the oxidative stress.…”
Section: Introductionsupporting
confidence: 49%
“…In our present study, the ingested arecoline by the larvae may be metabolized by the cytochrome P450s present in the gut of the larvae and exhibit toxicity. 11 The supplementation of arecoline along with the newly synthesized compound CL showed a marked reduction in cytotoxicity as well as genotoxicity. It may be due to the inhibition of cytochrome P450 by CL that may prevent/reduce the metabolic activation of arecoline by cytochrome P450.…”
Section: Assays For Determining the Protective Effect Of CL Against A...mentioning
confidence: 95%
“…[5][6][7][8][9] We have studied the toxicity of arecoline and the protective effect of natural plant products (Geraniol) in the third instar larvae as well as adult flies of the transgenic Drosophila melanogaster (hsp70-lacZ)Bg 9 . [10][11][12] The toxic effects of arecoline could be reduced by using natural plant products and the supplementation of various vitamins. 13 The charge transfer complexes (CTCs) are self-assembled organic materials formed from the interaction between donor and p-acceptor moieties through N + -HÁ Á ÁO À bonding, and this concept was first introduced by Mulliken and Foster.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As there is no permanent cure for the disease and the efficacy of the synthetic drugs also decline after some period of the treatment [10], the current research is now directed towards finding naturally occurring antioxidants of plant origin [11]. In this context, the unani system of traditional medicine is widely accepted in Indian sub continent and is practiced in India [12]. Majun Baladur (MB) is a polyherbal formulation, prescribed to patients having neurodegenerative ailments, under unani system of traditional medicine.…”
Section: Introductionmentioning
confidence: 99%